Pengaruh Konsentrasi Pupuk Cair (Mikroba Fungsional Tahan Salin) Terhadap Perkembangan Stek Daun Begonia rex “Silver Circle” - I PUTU AGUS HENDRA WIBAWA; I NYOMAN LUGRAYASA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
The Effect Of Liquid Fertilizer Concentration On Growths Of Leaf Cuttings Begonia Rex "Silver Circle" Begonia is one of the large genera in the Angiosperm group with asymmetrical leaf characteristics that are very suitable for ornamental plants. "Silver Circle" is the most popular type of Begonia rex. To ensure the availability of Begonia plants in large quantities, there is a need for propagation and cultivation. The success of plants propagation by cuttings is influenced by various factors, namely the type of cuttings and environmental factors including temperature and light humidity and nutrients from the growing media. The quality of planting media can be improved by functional microbial liquid fertilizer. Liquid fertilizer containing microbes functional can produce nutrients and growth hormones that can support plant growth. This study aims to determine the effect of liquid fertilizer concentration given, and also to determine the optimal liquid fertilizer concentration on the growth of B. rex leaf cuttings "Silver Circle". The treatment of liquid fertilizer gave significantly different results from controls on the parameters of leaf area and plant height. The most optimal dose of liquid fertilizer is 300 mL/L.